(untitled) (Research, Society and Development, 2021)
The present study aims to present a smart and sustainable packaging prototype for the transport of large nobreaks, in a real case study of a manufacturer of nobreaks from Diadema (SP). Through the case study, the study concluded that the construction and use of packaging are feasible and feasible, presents the technical characteristics of the packaging and a study of market and financial feasibility, in addition to its effects on the entire logistics design that involves these nobreaks. In addition, the study gives the scientific community a methodology for innovation, with a perspective for sustainability. Finally, it was possible to elaborate some actions linked to six of the Sustainable Development Goals - SDGs, established by the United Nations, which will be explored in the course of the study.